Computer-aided real-time kinematic global positioning system positioning technique deformation measurement and analysis [electronic resource] - Lee, Cheh Hang, 1981-; Halim Setan, supervisor; Fakulti Kejuruteraan dan Sains Geoinformasi (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2007